Enhanced microstructure, strength, and wear resistance of AA2024-AlB2 composites via multi-pass friction stir processing - Mahna Nikzad-Dinan; Roohollah Jamaati; Hamed Jamshidi Aval (Journal of Materials Research and Technology)
This study investigates the effect of multi-pass friction stir processing (FSP) on the microstructural, mechanical, and wear properties of AA2024 Al alloy reinforced with AlB2 particles. Cross-sectional analysis reveals a progressive improvement in particle distribution with additional FSP passes, attributed to increased strain rates and temperatures in the stir zone. Grain sizes within the stir zone expand as FSP passes increase from one to three, with values shifting from 1.2 ± 0.2 to 3.5 ± 0.2 μm. Samples with AlB2 reinforcement show finer grain sizes due to the pinning effect of particles, resulting in enhanced microstructural stability. X-ray diffraction analysis indicates an increase in AlB2 formation, rising from 6 % to 11 % with additional passes, driven by higher temperatures and strain in the stir zone. Hardness measurements reveal an increase from 120.3 ± 2.3 HV0.1 in the base metal to 158.7 ± 4.3 HV0.1 in AlB2-containing samples, attributed to uniform particle distribution and AlB2 formation. Tensile tests show improved yield strength and ultimate tensile strength in reinforced samples, with strength and toughness gains of approximately 25 % and 4 % after three passes. Wear tests show decreased friction coefficients and wear rates in AlB2-containing samples, with rates reducing to 4.5 μg/m, highlighting the wear-resistant properties imparted by AlB2 particles.